1997
DOI: 10.1007/s002280050364
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events and discomfort in studies on healthy subjects: the volunteer's perspective

Abstract: Adverse events and inconveniences are inherent to nontherapeutic studies in healthy subjects. From the volunteer's perspective it appears that the incidence of adverse experiences in such studies exceeds the reported frequencies from investigators considerably. This finding suggests that investigators are usually not aware or able to ascertain the true incidence of adverse events. The present survey also confirms that pertinent information on the personal history may be unreliable. Volunteers are reluctant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Admittedly, the importance displayed regarding the monetary compensation was no surprise, as these results concur with those found in other studies (Hasser et al , 1977; Bigorra & Banos 1990, Hermann et al. 1997).…”
Section: Discussionsupporting
confidence: 92%
“…Admittedly, the importance displayed regarding the monetary compensation was no surprise, as these results concur with those found in other studies (Hasser et al , 1977; Bigorra & Banos 1990, Hermann et al. 1997).…”
Section: Discussionsupporting
confidence: 92%
“…Of the twelve 13-24 studies identified, six were conducted in the United States, 15-17, 19, 22, 24 five in Europe, 13, 14, 20, 21, 23 and one in Malawi. 18 The Mtunthama study, which took place in Malawi, was the only published research on this topic from a developing country identified by our review.…”
Section: Resultsmentioning
confidence: 99%
“…13-16, 21-24 Access to healthcare was the main reported motivation in the Mtunthama study, 18 as well as the main incentive for the elderly volunteers studied by van Gelderen et al 20 Helping to contribute to science and medicine, 13, 15, 19, 21, 23 helping others, 15-17, 19-23 meeting people, 17 relaxing 17 or wanting to participate in something important, 19 learning more about science and medicine, 14, 16, 17 and curiosity 13, 14, 16, 18, 19 were other reported motivations for participation (Table 2, Table 4). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations